1987
DOI: 10.1073/pnas.84.14.4994
|View full text |Cite
|
Sign up to set email alerts
|

Specific cellular immune response and neutralizing antibodies in goats immunized with native or recombinant envelope proteins derived from human T-lymphotropic virus type IIIB and in human immunodeficiency virus-infected men.

Abstract: Animals immunized with native or recombinant envelope proteins from the human immunodeficiency virus (HIV, formerly referred to as human T-lymphotropic virus type III) human T-lymphotropic virus type IIIB and naturally HIV-infected men were assessed for neutralizing antibodies and cell-mediated immunity toward the virus. Immunization of rabbits or goats with the native external envelope glycoprotein gpl20 or with corresponding recombinant proteins elicited strictly type-speciflic neutralizing antibodies. A bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Recently Zarling et al (17) demonstrated T-cell responses to gpl20 in macaques, and Cease et al (18), employing an emphipathic helix model, demonstrated Thelper sites on env peptides in mice. In an animal model, Krohn et al (19) observed T-cell proliferative responses to native gpl20 but not to recombinant env peptides. The lack ofT-cell responses to recombinant peptides may be due to the lack of immunogenic epitopes in the preparation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Zarling et al (17) demonstrated T-cell responses to gpl20 in macaques, and Cease et al (18), employing an emphipathic helix model, demonstrated Thelper sites on env peptides in mice. In an animal model, Krohn et al (19) observed T-cell proliferative responses to native gpl20 but not to recombinant env peptides. The lack ofT-cell responses to recombinant peptides may be due to the lack of immunogenic epitopes in the preparation.…”
mentioning
confidence: 99%
“…Briefly, wells of polystyrene plates were coated with 0.1 ml of heavy chain-specific rabbit anti-human IgG diluted to 2 gg/ml in 0.05 M sodium carbonate (pH 9.6) containing 0.02% sodium azide. The plates were sealed, incubated at room temperature for [16][17][18][19][20] Fig. 3 demonstrate that human PBMC precultured with 5-200 ng of the env-gag protein per ml produced significant levels of IgG.…”
mentioning
confidence: 99%
“…HIV-1 neutralizing antibodies have been raised in experimental animals using native (5) and recombinant gp4l and gpl20 (1,6). Synthetic peptides derived from these proteins have been used as immunogens and have been shown to elicit a neutralizing antibody response (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The HIV determinants carried by recombinant 8 induced a better immune response than those carried by recombinant 2. According to the lower proportion of the fused protein in recombinant 8 (29), using a fused protein produced in E. coli carrying an overlapping sequence, also obtained neutralizing antibodies and a specific cellular immune response. In our HBsAg expression system, the proteins are normally glycosylated and this could be very important in eliciting high-affinity antibodies needed to block the interaction of the HIV envelope protein with the CD4 receptor.…”
Section: Discussionmentioning
confidence: 99%